Sago Porridge Enriched with Red Dragon Fruit (Hylocereus polyrhizus) Extract: A Functional Food with Enhanced Sensory and Nutritional Properties - Putra, I Gede Arie Mahendra; Rna Fajarini, Luh Dian; Dewi, Putu Julyantika Nica; Muzakki, Wafi Adizara; Ibrahim, Nur Syamsi (Journal of Agri-Food Science and Technology, 2025)
Sago, one of Indonesia’s staple foods, holds significant potential for food diversification due to its high carbohydrate content. However, despite its nutritional benefits, sago consumption remains less popular than corn and potatoes. Sago porridge, a traditional food product, can be developed into a healthy alternative, but its translucent brown color is visually unappealing, affecting consumer acceptance. This study aims to evaluate the optimal concentration of red dragon fruit extract as a natural colorant to enhance the visual appeal of sago porridge. The research method involved testing varying concentrations of red dragon fruit extract (0%, 2%, 4%, 6%) through sensory evaluation and physical analysis. Results showed that a 6% concentration yielded the highest acceptability, with the following physical properties: strawberry red color (L*:48.4; a*:70.8; b*:21.5), viscosity of 56,000 mPas, texture force of 8.7980 N, and pH of 7.21. This study contributes through the innovative use of red dragon fruit extract as a natural colorant, improving both the visual appeal and nutritional value of sago porridge. The optimal 6% concentration provides a practical reference for local food industries to produce value-added products, supporting food diversification based on local resources and aligning with global trends in healthy, natural foods.